Pattern of Rheumatological Diseases in Children in A Tertiary Care Hospital of Bangladesh - Yusuf, Mir Mohammad; Saha, Shovon (Dhaka Shishu (Children) Hospital Journal, 2026)
Background: The spectrum and importance of Rheumatic Diseases in children are increasing day by day globally as well as at national level. These diseases are chronic intractable considered as important cause of childhood morbidity and disability. Objective: To estimate the pattern of different types of rheumatologic diseases in Pediatric Rheumatology Department of Bangladesh Shishu Hospital & Institute. Method: A retrospective study was done in the department of Pediatric Rheumatology unit from July 2022 to June 2023. Data were collected from the departmental registry. Results: A total of 58 patients were enrolled. Highest number of patients had JIA (59%) followed by pediatric systemic vasculitides (17.24%) and SLE (8.6%). Among vasculitides, IgA vasculitis [Henoch–Schönlein purpura (HSP)] was predominant (8.6%) followed by Kawasaki Disease (5.2%), ANCA-associated vasculitis (AAV-1.7%), Polyarteritis nodosa (PAN-1.7%). Juvenile dermatomiositis (JDM) and systemic sclerosis (SS) was found in 3.4% and 1.7% cases respectively. Septic arthritis and reactive arthritis was also found in 6.9% and 3.4% cases. Polyarticular JIA was the commonest type (20.7%) in this series, followed by systemic onset, enthesitis related arthritis (ERA) and oligoarthritis. Conclusion: Juvenile Idiopathic Arthritis (JIA) was the most prevalent paediatric rheumatologic condition in this study, followed by systemic vasculitides and systemic lupus erythematosus (SLE). Among the vasculitides, Henoch–Schönlein purpura (IgA vasculitis) and Kawasaki disease were most frequently observed. DS (Child) H J 2024; 40(1): 25-29